‘Finishing that plate of food …’ The role of the nurse caring for the patient with dysphagia - Jaishika Seedat; Nikki Strime (The South African Journal of Clinical Nutrition, 2022)
Objective: Dysphagia is a ‘hidden’ disorder that can present with a range of consequences including fatality. It is important for intervention to be timeous and adopt a team approach, with each professional displaying understanding of both dysphagia and each other’s roles. The nurse is at the epicentre of service provision in hospitals and is ideally positioned to collaborate with the speech-language therapist to manage dysphagia. The state of collaboration, however, is not ideal. Reasons perpetuating this need, to be understood to facilitate improved care by nurses for patients with dysphagia. Design: The aim of the study was to describe the caseload of dysphagia patients seen by nurses, their experiences caring for patients with dysphagia, and nurses’ views on inter-professional training. Setting: A qualitative, exploratory study was conducted with nurses working at two government hospitals in Johannesburg, South Africa. Subjects: An open-ended semi-structured interview was conducted with nine nurses working with adult patients. Descriptive and inductive thematic analysis was used, comparisons were made between the responses, and data were categorised according to emerging themes. Results: Results confirmed that while experience improved care, gaps in dysphagia knowledge, inexperience and contextual challenges adversely impacted efficiency of dysphagia care. Inter-professional training and recognition of nurse intervention positively impacted on interactions with dysphagia. Conclusion: Nurses have a central role in dysphagia care in acute settings. The study confirmed that multidisciplinary management, inter-professional training and inter-professional relations contribute to overall improved service delivery in dysphagia in acute settings, with nurses at the epicentre.